Looking at proteins from two dimensions: a review on five decades of 2D electrophoresis. (December 2014) - Westermeier, Reiner
Abstract Separating proteins according to two different gel-electrophoretic methods not only increases the resolution power for highly complex samples when compared to one-dimensional separations, but is also a valuable tool for protein and protein complex characterization. There are a number of different electrophoresis methods which can be combined. The combination of isoelectric focusing under denaturing conditions and SDS polyacrylamide gel electrophoresis delivers the highest resolution of all bio-analytic techniques. This is a short review on the history and state of the art of two-dimensional electrophoresis methods, and contains some practical tips for high resolution 2D electrophoresis, which are based on several decades of experience with this method.